Vertical Product Differentiation and the Import Demand Function: Theory and Evidence - Jim Malley; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we use a model of vertical product differentiation to cast doubt on the general validity of the import demand function as specified in macroeconomic models. The empirical importance of our theoretical concerns is then examined with the aid of two hypotheses. According to the first hypothesis, an increase in domestic wages is expected to reduce the share in total imports for goods in which the domestic comparative advantage is in high quality varieties of these goods. The second hypothesis states that an increase in non-wage income will increase the share of a good's imports if the country has comparative advantage in high quality varieties of this good. We find considerable empirical support for both hypotheses in the data for Germany, Japan and the United States.
Keywords: 330